IMPLEMENTASI TEORI DONALD E. SUPER PADA PROGRAM PELAYANAN BIMBINGAN KARIR UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Nina Fitriyani; Riska Handayani; Dwinda Tiara Putri; Dede Rahmat Hidayat (Jurnal Ilmu dan Budaya, 2019)
The purpose of the BK career service at school is for students to know (describe) self-characteristics (interests, values, abilities and personality traits) from which all learners can identify areas of study and career appropriate With him, students gain an understanding of things related to the career world in which they are included, learners are able to identify various areas of education available that are relevant with various fields of work. There is a career in junior high School (SMP) there is a stage of growth in career selection based on individual stages of development, and preparing students early so as not to experience mistakes in future careers. In Donald E. Super's theory of age growth (0-14 years) begins physical and psychological growth, at this stage individuals begin to form attitudes and behavioural mechanisms that will then become important in their concepts. While the exploration phase of age (15-18 years) This stage began since the individual realized that the work is an aspect of human life. Individuals think of various career alternatives, but have not yet taken binding decisions. At this stage individuals begin to conduct self-study to try different roles, as well as to perform job browsing. The role of career guidance and counseling as an integrated as an ability and intellectual skill and special skills up to the maturity of a specific career. The presence of a Career guidance service program is to prepare, introduce, and provide information to students.